The history of the Pelagonians. State of research - Pająkowski, Włodzimierz (Balcanica Posnaniensia. Acta et studia, 1990)
The article analyzes the state of research on the history of the Pelagonians, a people inhabiting areas neighboring ancient Macedonia, whose history remains poorly known. The problem is significant due to the fragmentary and ambiguous nature of the sources and numerous contradictions in previous interpretations. The aim of the work is a critical analysis of available sources and existing research concepts, as well as an attempt to reconstruct the history of the Pelagonians. The author uses the method of criticism of written sources (including Homer, Athenian inscriptions, and later historical accounts) and the analysis of historiographical output. The most important results indicate that sources concerning the Pelagonians are scarce and include mainly inscriptions from the 4th century BC, which confirm the existence of an independent kingdom of the Pelagonians and their contacts with Athens. The author critically evaluates earlier hypotheses, especially those linking the Pelagonians with the Lynkestian dynasty or assuming their conquest by the Paeonians, pointing to the weakness of arguments based on onomastics or numismatics. The analysis suggests that Pelagonia in the 4th century BC was an independent political organism, which later came under the influence of stronger neighbors, first the Paeonians or Illyrians, and ultimately Macedonia. The conclusion is the need for a cautious approach to reconstructing the history of the Pelagonians and recognition of them as a distinct political entity in the region, whose history requires further research and critical reinterpretation of sources.